Smartphone Use For Mathematic Study In Class IV SDN Kaliwungu 1 Jombang - Bahrudin; Dwi Rochmania, Desty (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The advent of the digital age has changed the systems and patterns of life in education so that indirectly students are influenced by their learning interests. So from that the role of teachers and parents is expected to be a solution and control for students. Therefore, the research aims to find out the use of smartphones on the learning interests of students of class IV SDN Kaliwungu 1 Jombang. Research uses discreet methods through a qualitative approach. Research results show that the use of smartphones in fourth grade students affects the interest in learning mathematics. This is demonstrated by the form of learning mathematics through digital video and quis done at school. And the school also gave an instruction to parents to participate in the event of students' learning development.